Segmentation the Tumor from the Brain Depending on the Colour - Hasan Dakheel, Awfa; ., . (International Journal of Engineering and Technology, 2018)
The objective of this study is to present a method that aids in the diagnosis of abnormality in brain due to tumors from MRI brain image whereby segmenting the brain tumor is done by using a novel algorithm that depends on the colour of the 2D image. Therefore, this work consists of three main stages, the first one is loading image into memory, and then the segmentation algorithm is applied. Finally, in order to obliterate the noise object, the 2D median algorithm is conducted. After applying the method the results which are obtained show better output to determine the tumor, simultaneously the diameter of the tumor can be calculated.Â Â